PERANCANGAN BUKU CERITA BERGAMBAR PUTI SARI BANILAI KABUPATEN LIMAPULUH KOTA - FAJAR WAHYU PUTRA, Ir. Drs. Heldi, M.Si., Ph.D., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Media print information one of the communicative media that provides a message for the audience, print media publications have been left with the media information and technology. The effect of this development on the power and interest of dolescent reading. The print media through traditional folklore books is now less attractive for most people, especially teenagers in the District of Lima Puluh Kota. Aim. designing a picture book Puti Sari Banilai is to increase interest in reading, opening insights, and participate in the achievement of the folk traditions of folklore region of Lima Puluh Kota District. Design using descriptive methodology with 5W1H analysis approach (what, where, when, who, why, how). The main media in the writing of this book is pictorial and supporting media in this design the author uses x-banner supporting media, pins, stickers, calendars, hats, t-shirts, and clocks.Keywords: Folklore, Puti Sari Banilai, Pictorial Story